Bis‐Alkoxycarbonylation of Acrylic Esters and Amides for the Synthesis of 2‐Alkoxycarbonyl or 2‐Carbamoyl Succinates. Issue 3 (14th October 2019) - Olivieri, Diego; Tarroni, Riccardo; Della Ca', Nicola; Mancuso, Raffaella; Gabriele, Bartolo; Spadoni, Gilberto; Carfagna, Carla
Abstract: The first example of the bis‐alkoxycarbonylation of acrylic esters and acrylic amides, leading to differently substituted 1, 1, 2‐ethanetricarboxylate compounds and 2‐carbamoylsuccinates respectively, is reported. The catalyst is formed in situ by mixing Pd(TFA)2 (TFA=trifluoroacetate) and the ligand bis(2, 6‐dimethylphenyl)butane‐2, 3‐diimine. The reaction, that proceeds using p ‐benzoquinone as oxidant and p ‐toluenesulfonic acid as additive, has been applied to variously substituted electron‐poor alkenes, employing different alcohols as nucleophiles, under very mild reaction conditions (4 bar of carbon monoxide at 20 °C). Remarkably, this catalytic system is able to promote the carbonylation of both the β‐ and the generally unreactive α‐positions of acrylic esters and amides, allowing the formation of bis‐alkoxycarbonylated products in good to excellent yields (up to 98%). The trend of reactivity, observed with the different electron‐deficient olefins, has been rationalized on the basis of the proposed catalytic cycle and DFT calculations. Abstract :